2016
DOI: 10.1093/gbe/evw213
|View full text |Cite
|
Sign up to set email alerts
|

TRT, a Vertebrate and ProtozoanTc1-Like Transposon: Current Activity and Horizontal Transfer

Abstract: We report a Danio rerio transposon named DrTRT, for D. rerio Transposon Related to Tc1. The complete sequence of the DrTRT transposon is 1,563 base pairs (bp) in length, and its transposase putatively encodes a 338-amino acid protein that harbors a DD37E motif in its catalytic domain. We present evidence based on searches of publicly available genomes that TRT elements commonly occur in vertebrates and protozoa. Phylogenetic and functional domain comparisons confirm that TRT constitutes a new subfamily within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…S1). Then, 19 representative IS630 transposase sequences including the 11 clades, Tc1/mariner transposase families identified previously [ 21 23 , 26 , 42 47 ], and Zator transposases, which were defined as a superfamily close to ITm group [ 28 ], were combined with all identified pogo transposases to infer a phylogenetic tree by using maximum likelihood methods with the IQ-TREE program [ 48 ]. The resulting tree shows that although pogo , Tc1/mariner (including DD34E/ Tc1 , DD35E/ TR , DD36E/ IC , DD34D/ mariner , DD37D/ maT , DD37E/ TRT , DD37D, DD39D, and DD41D), Zator , and DD34E/ Gambol transposases are sister clades, they formed four distinct highly supported monophyletic clades, with 74, 99, 92, and 100% bootstrap supports for pogo , Zator , Tc1/mariner , and DD34E/ Gambol clades respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1). Then, 19 representative IS630 transposase sequences including the 11 clades, Tc1/mariner transposase families identified previously [ 21 23 , 26 , 42 47 ], and Zator transposases, which were defined as a superfamily close to ITm group [ 28 ], were combined with all identified pogo transposases to infer a phylogenetic tree by using maximum likelihood methods with the IQ-TREE program [ 48 ]. The resulting tree shows that although pogo , Tc1/mariner (including DD34E/ Tc1 , DD35E/ TR , DD36E/ IC , DD34D/ mariner , DD37D/ maT , DD37E/ TRT , DD37D, DD39D, and DD41D), Zator , and DD34E/ Gambol transposases are sister clades, they formed four distinct highly supported monophyletic clades, with 74, 99, 92, and 100% bootstrap supports for pogo , Zator , Tc1/mariner , and DD34E/ Gambol clades respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria IS256 transposase was used as outgroup. Then, the representative sequences of IS630 transposases from each clade and other unclassified sequences, Tc1/mariner known families transposases [ 21 23 , 26 , 42 47 ], and Zatror transposases [ 28 ] were jointed with the pogo transposases to infer the phylogenetic tree based on the multiple amino acid alignment of the conserved DDE domain by using the maximum likelihood method within IQ-TREE [ 48 ]. The best-fit model was selected by ModelFinder embedded in IQ-TREE [ 48 ], and the reliability of maximum likelihood trees was estimated by using the ultrafast bootstrap approach with 1000 replicates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification of ITm elements is based on phylogenetic analysis and, until recently, it was well correlated with structural features (the length of peptide chain between the second and the third amino acid residues of the catalytic DDE/D triad (Tellier et al 2015). However, the recent studies have identified, at least, four different groups of ITm elements with DD37E signature: mosquito (Shao and Tu 2001), TRT (Zhang et al 2016a), L18 and L31 (Puzakov et al 2018). Thus, the families of ITm elements cannot be accurately distinguished by the spacer size of DDE/D domains.…”
Section: Introductionmentioning
confidence: 99%